Understanding bio-mechanics of intrusion: an orthodontics review - Sharma, Disha; Thakur, Gaurav; Gurung, Deepak; Thakur, Amrita (International Journal of Research in Medical Sciences, 2024)
Orthodontic intrusion is a common treatment approach in managing orthodontic esthetic and functional problems, including gummy smile and deep bite. Intrusion often constitutes an integral part of orthodontic treatment to improve sagittal and vertical incisor relationships, to correct interincisal angle and, consequently, the gingival line and restore the esthetics of smiling. The choice of appliances and techniques used by practitioners varies radically among individuals, but the fundamental forces and moments they produce are universal. Appliances will always act according to the laws of physics. Therefore, understanding the basic biomechanical principles of intrusion may help in effecting efficient tooth control and help in achieving successful orthodontic treatment outcomes more predictable and consistent.